(untitled) (Journal of Fiber Bioengineering and Informatics, 2023)
Seamless knitting technology involves knitting diverse tissue structures in the same three-dimensional knitted fabric in horizontal and vertical rows without forming seams, and the transition tissues are typically used for fabric tissues with significant differences in properties, however, it is usually easy to be overlooked in research. Three types of three-dimensional knitted fabrics were transformed in terms of tissue structure and increasing percentage. An AMI airbag contact pressure measurement system was used to establish pressure models with three different diameters of gum cotton cylinders to measure the interfacial pressure of the fabrics to study the effect of transitional tissue on the compression performance of three-dimensional knitted fabrics under tensile load. The study found that when the fabric stretch rate was at 0%, 25%, 50%, and 75%, the fabric stretch rate and pressure were positively correlated; the fabric tissue composition and number of components had a significant effect on the pressure, and the increase in the number of components caused the pressure at the tissue junction to increase significantly. This study aims to lay the groundwork for winter knitted sportswear pattern development and compression performance optimization.